Serum Magnesium Level in Eclamptic Patients In a Tertiary Care Hospital (Journal of Chittagong Medical College Teachers' Association, 2017)
Magnesium deficiency during pregnancy has been reported to be associated with eclampsia. This descriptive cross sectional study carried out in Obstetrics and Gynecology Department of Chittagong Medical College Hospital from September 2013 to August 2014. The objective of the study was to estimate the serum magnesium level in eclamptic patients. Serum magnesium level of 80 eclamptic patients and 80 healthy pregnant women (Age and gestational age matched) were measured and compared to evaluate the association between hypomagnesaemia and eclampsia. All the necessary information and clinical data were recorded in predesigned questionnaires and analyzed using SPSS. t-Test and Chi-square test were used for comparison of quantitative and qualitative data respectively. For analytical test the level of significance was 0.05 (‘p’ value